Disinfection of the Access Orifice in NOTES: Evaluation of the Evidence Base. (12th July 2011) - Sodergren, Mikael H.; Pucher, Philip; Clark, James; James, David R. C.; Sockett, Jenny; Matar, Nagy; Teare, Julian; Yang, Guang-Zhong; Darzi, Ara
Abstract : Introduction . Appropriate prevention of infection is a key area of research in natural orifice translumenal endoscopic surgery (NOTES), as identified by the Natural Orifice Surgery Consortium for Assessment and Research (NOSCAR). Methods . A review of the literature was conducted evaluating the evidence base for access orifice preparation/treatment in NOTES procedures in the context of infectious complications. Recommendations based on the Oxford Centre for Evidence-Based Medicine guidelines were made. Results . The most robust evidence includes several experimental randomised controlled trials assessing infectious complications in the transgastric approach to NOTES. Transvaginal procedures are long established for accessing the peritoneal cavity following disinfection with antiseptic. Only experimental case series for transcolonic and transvesical approaches are described. Conclusion . Grade C recommendation requiring no preoperative preparation can be made for the transgastric approach. Antiseptic irrigation is recommended for transvaginal (grade C) NOTES access, as is current practice. Further human trials need to be conducted to corroborate the current evidence base for transgastric closure. It is important that future trials are conducted in a methodologically robust fashion, with emphasis on clinical outcomes and standardisation of enterotomy closure and postoperative therapy.